Electrical impedance of lithium nickel cobalt oxides doped with aluminium - Sethuprakhash, V.; Basirun, Wan Jefrey (Taylor & Francis, 2011)
Three types of lithium nickel cobalt oxides doped with aluminium have been synthesised by a solid state reaction at 800 degrees C for 18 h. The compounds were analysed using X-ray diffraction and gave sharp and well defined peaks. Electrical impedance spectroscopy was performed on all three materials, and conductivity measurements gave negative activation energies, which increased with the aluminium content. The largest variation in conductivities with temperature was found with the material with the highest aluminium content. Conductivity decreased with the increase in aluminium for all temperatures.